Crown budding: A method to reduce cost of production of Natural rubber in India - Pillai P N R; Edathil T T; Krishnankutty V (Placrosym VII, Coonoor, 1986. Journal of Plantation Crops, 16(Supplement):277-279)
Since the abnormal leaf fall disease of rubber caused by Phytophthora spp. is very severe and debilitating, crown budding of high yielding susceptible clones, viz., GT 1, RRIM 600 and RRIM 628 with disease resistant/tolerant vlones viz., F 4542, FX 516 and RRII 33 was tried to combat the disease. Leaf retention against abnormal leaf fall disease of unsprayed crown budded plants was very good when compared to sprayed control plants. The yield of RRIM 600 and RRIM 628 crown budded plants was higher than control plants whereas yield of GT 1 crown budded plants was found to be lower in the cases of all the three crown clones. Though, the crown budding appears to be a promising method in the control of abnormal leaf fall disease, further experimental data for all available high yielding clones are necessary for making general recommendation of this technique.
Keywords: Abnormal leaf fall disease; Crown budding